Geochemical Characterization of Groundwater in a Volcanic System - Carmelo Bellia; Adrian H. Gallardo; Masaya Yasuhara; Kohei Kazahaya (Resources, 2015)
A geochemical investigation was undertaken at Mt. Etna Volcano to better define groundwater characteristics of its aquifers. Results indicate that the Na–Mg ± Ca–HCO3− ± (SO42− or Cl−) type accounts for more than 80% of the groundwater composition in the volcano. The remaining 20% is characterized by elevated Ca2+. Waters along coastal areas are enriched in SO42− or Cl−, mainly due to mixing with seawater and anthropogenic effects. The majority of the samples showed values between −4‰ to −9‰ for δ18O and −19‰ to −53‰ for δ2H, suggesting that precipitation is the predominant source of recharge to the aquifers, especially in the west of the study area. The analysis of δ13C and pCO2 shows values 1 to 3 times higher than those expected for waters in equilibrium with the atmosphere, suggesting a partial gas contribution from deep sources. The diffusion of gasses is likely to be controlled by tectonic structures in the volcano. The ascent of deep brines is also reflected in the CO2 enrichment (up to 2.2 bars) and enriched δ2H/δ18O compositions observed in the salt mounts of Paternò.